Effect of hydrotherapy on the signs and symptoms of delayed muscle soreness - Vaile, J.; Halson, S.; Gill, N.; Dawson, B. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The purpose of this study was to examine the effects of three hydrotherapy interventions on the physiological and functional symptoms of delayed onset muscle soreness (DOMS). A total of 38 strength trained males completed two experimental trials separated by eight months in a randomised crossover design; one trial involved passive recovery (PAS, control), the other a specific hydrotherapy protocol. Subjects were randomly assigned to one of three groups differing only in recovery intervention: 1) cold water immersion (CWI, 15 C), 2) hot water immersion (HWI, 38 C) or 3) contrast water therapy (CWT, 15 C/38 C). For each trial subjects performed a DOMS-inducing leg press protocol consisting of 5x10 eccentric contractions at 120% one repetition max (1RM), followed by 2x10 eccentric contractions at 1RM, with three minutes rest between sets. Weighted squat jump, isometric squat, perceived pain, thigh girths and blood variables were measured prior to, immediately after, then 24, 48 and 72 hours post-exercise. Following testing on each day subjects completed one of the recovery interventions (CWI, HWI, CWT or PAS) for 14 minutes. Recovery of squat jump performance was significantly enhanced (P<0.05) at 24, 48 and 72 hours post exercise following CWT (mean difference from baseline expressed as a percentage; -6.2, -3.1, 0.3%) when compared to PAS (-14.5, -12.3, -7.5%) and at 48 and 72 hours post-exercise following CWI (-5.8, -1.9%) when compared to PAS (-15.9, -7.3%). Additionally, recovery of isometric force was significantly greater at 24, 48, and 72 hours post-exercise following CWT (-10.3, -7.4, -2.8%) and HWI (-12.8, -10.1, -3.2%) and also significantly improved at 48 and 72 hours post-exercise following C WI (-7.3, -4.3) compared to PAS. Significant decreases in mid thigh girth were observed at 24, 48, and 72 hours post-exercise following both CWI (0.7, 0.4, 0.3%) and CWT (0.5, 0.2, 0.1%) compared to girth measurements following PAS ( 0.8- 1.5%) and HWI ( 0.5-1.3%). Perceived pain was only improved (P<0.01) following CWT at 24, 48 and 72 hours post-exercise. The only significant reduction (P<0.05) in any of the blood markers monitored was observed in Creatine Kinase concentration at 24 and 72 hours post-exercise following CWI. Both CWT and CWI were associated with a smaller reduction and faster restoration of isometric force and squat jump performance. While HWI improved isometric force production, no beneficial effects were observed in squat jump performance over time. Compared to PAS and HWI, CWT and CWI appeared to reduce localised oedema that has been associated with DOMS. In conclusion, CWT and CWI recovery interventions appear able to reduce, and improve recovery from, the physiological and function symptoms associated with DOMS.